GPCR Inhibitors Have Antiviral Properties against JC Polyomavirus Infection - Amanda L. Sandberg; Avery C. S. Bond; Lucas J. Bennett; Sophie E. Craig; David P. Winski; Lara C. Kirkby; Abby R. Kraemer; Kristina G. Kelly; Samuel T. Hess; Melissa S. Maginnis (Viruses, 2024)
JC polyomavirus (JCPyV) infects the majority of the population and initially establishes a persistent but asymptomatic infection of the kidneys. In healthy individuals, the infection remains controlled by the host immune system, but for individuals experiencing prolonged immunosuppression, the infection can reactivate and spread to the brain, where it causes progressive multifocal leukoencephalopathy (PML), which is a fatal neurodegenerative disease. Currently, there are no approved therapies to treat PML, and affected individuals suffer rapid motor weakness and cognitive deterioration. To identify novel therapeutic treatments for JCPyV infection, receptor agonists/antagonists identified in a previously published drug screen were evaluated for their antiviral properties. Seven drugs were selected and validated using infectivity assays, and the mechanism of inhibition was further explored for G protein coupled receptor (GPCR)-associated inhibitors due to the role of the GPCR 5-hydroxytryptamine 2 receptors (5-HT2Rs) in JCPyV entry. The inhibitors cetirizine and paroxetine both reduced infection early in the JCPyV infectious cycle. Paroxetine specifically reduced viral internalization through altering the receptor density of 5-HT2CR, inhibiting β-arrestin recruitment to the receptor, and reducing MAPK signaling through ERK. These findings highlight the potential of receptor signaling and viral entry mechanisms as possible targets for antiviral drug development. Further, this research suggests that FDA-approved receptor agonists/antagonists currently used to treat other medical conditions could be repurposed into antivirals for the possible treatment of JCPyV infection and the fatal disease PML.